ANALISIS JENIS TANAH UNTUK PENENTUAN KAWASAN RESAPAN AIR KELURAHAN KAPUK, KECAMATAN CENGKARENG JAKARTA BARAT: ANALYSIS OF SOIL TYPE FOR DETERMINATION KAPUK DISTRICT WATER ABSOLUTE AREA, CENGKARENG DISTRICT, WEST JAKARTA - Ahmad, Riduan; Anugrahadi, Afiat; Yuda, Himmes Fitra (Journal of Geoscience Engineering and Energy, 2024)
Water catchment areas in residential areas or in the process of development are very important. The need for water resources that are used to meet the basic needs of personal life as well as development needs that are still growing really need water in the process of infrastructure development Soil type is one of the factors that determines water catchment areas. Soil samples were taken in the study area and then tested in the laboratory to determine the physical properties and classify the types of soil present. The results of the research are that the type of soil in the study area based on USCS is of poor gradation and the type of soil is based on PU No. 02/2013 has a score of 5.